A problem of inner and social isolation of the individual in B. D. Grinchenko’s literary heritage (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article deals with the forms of solitude problem realization as a manifestation of human being contradiction in B. D. Grinchenko’s prose and poetry. The authors emphasize the ways of depiction of characters at state of psychological affectation.
Keywords: prose; poetry; solitude problem; psychological affectation